BE NUMBER ONE, BE THE BEST, SAYS USM VC - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 1 September 2016 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato' Dr. Omar Osman today urged the students and staff of the university to always aspire to be number one and be the best.